2003
DOI: 10.1105/tpc.006882
|View full text |Cite
|
Sign up to set email alerts
|

The eto1, eto2, and eto3 Mutations and Cytokinin Treatment Increase Ethylene Biosynthesis in Arabidopsis by Increasing the Stability of ACS Protein

Abstract: The Arabidopsis ethylene-overproducing mutants eto1 , eto2 , and eto3 have been suggested to affect the post-transcriptional regulation of 1-aminocyclopropane-1-carboxylic acid synthase (ACS). Here, we present the positional cloning of the gene corresponding to the dominant eto3 mutation and show that the eto3 phenotype is the result of a missense mutation within the C-terminal domain of ACS9, which encodes one isoform of the Arabidopsis ACS gene family. This mutation is analogous to the dominant eto2 mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
394
2
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(416 citation statements)
references
References 41 publications
15
394
2
5
Order By: Relevance
“…DPBA fluorescence was examined in the ethylene-overproducing1 (eto1) mutant (Chae et al, 2003) and enhanced flavonol accumulation was observed in the guard cells (Fig. 2).…”
Section: Elevated Ethylene Levels Through Exogenous Treatment or In Tmentioning
confidence: 99%
“…DPBA fluorescence was examined in the ethylene-overproducing1 (eto1) mutant (Chae et al, 2003) and enhanced flavonol accumulation was observed in the guard cells (Fig. 2).…”
Section: Elevated Ethylene Levels Through Exogenous Treatment or In Tmentioning
confidence: 99%
“…The respective GST fusion proteins were isolated using Glutathione Sepharose 4 Fast Flow medium according to the manufacturer's directions (Amersham Biosciences). ACS5 was purified as described (Chae et al, 2003). Myelin basic protein was purchased from Sigma-Aldrich.…”
Section: Protein Kinase Assaysmentioning
confidence: 99%
“…At 32°C, exogenous auxin (NAA) and cytokinin (BAP) and endogenously produced ethylene are all required for cell survival (Roberts et al, 1995;Gushwa et al, 2003). We speculate that NAA and BAP are both required for survival at 32°C because cytokinin stabilizes the 1-aminocyclopropane-carboxylic acid synthase (ACS) protein (Chae et al, 2003) that results from auxin-mediated induction of ACS genes (Abel et al, 1995;Abel and Theologis, 1996;Merritt et al, 2001;Tanaka et al, 2006), thereby optimizing ethylene production required for protoplast survival at 32°C. After 24 h of preincubation at 38°C, none of these growth regulators are required for GCP to survive in culture at 32°C (Gushwa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%